Dampak Dari Budaya Organisasi Dan Motivasi Terhadap Kinerja Pegawai - Sinta Nugraheni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the impact of organizational culture and motivation on employee performance in the work environment. Organizational culture includes the values, norms, and beliefs that shape the identity of an organization, while motivation refers to the internal and external drives that drive individuals to achieve their goals. This research uses a quantitative approach through surveys and statistical data analysis to determine the relationship between organizational culture, motivation and employee performance. The research results show that a strong and positive organizational culture can increase employee motivation, which in turn contributes to improving their performance. Factors such as leadership, organizational communication, and recognition of achievements also play a key role in influencing the relationship between organizational culture, motivation, and employee performance. The managerial implications of these findings include the importance of building an organizational culture that supports and motivates employees to achieve organizational goals.